(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
Between 1938 and 1942 the Mostra dell’Abitazione Italiana (Italian Housing Exhibition, IHE), was planned and designed as a special sector of the E42 programme. Intended to present to the widest international audience the quality of the housing of the upper bourgeoisie of an ideal ‘new Fascist City’, it was programmed and designed as an experimental application of the new urban planning concepts and regulations. In this framework the young Ludovico Quaroni was engaged with the design of two Villas for eminent people, villa Gagliani and Villa Tuccimei. Both designs deal with the research of ‘an other modernity’, Mediterranean synthesis of vernacularity and classicism. Villa Gagliani design is openly depending on the Le Corbusier line of ‘vernacular’ modernity represented, for example, by the Villa ‘le Sextant’ at Mathes. Villa Tuccimei design, on the contrary, is a passionate investigation about the possibility to pursue a modern, Mediterranean and classical architecture. At the centre this Quaroni’s investigation is the architectural order as to conclude the experience began with the Piazza Imperiale project.